Foramen of Huschke persistence in Brazilian adult temporal bones: a morphometric study - Silva, Wagner Gomes da; Ramos, Amanda Barreto; Gomes, Bianca Silva; Kühlman, Deise Caldas; Chávez, José Gabriel; Fernandes, Luciana Quintanilha Pires; de-Vasconcellos, Henrique Ayres (Journal of Oral Diagnosis, 2018)
Foramen of Huschke (FH) is a normal anatomical structure performed until the total maturation of the cranium skeleton, which obliterates by a natural process about the 5-year- old. However, it may persist in adult life and can be rarely associated with complications in the temporomandibular joint (TMJ) and external auditory canal apparatus as well as a higher risk of tympanic injury during surgical procedures such as TMJ arthroscopy. The aim of this study was to report the prevalence and morphometric features of persistent FH in a Brazilian adult temporal bones sample. The methods included an anatomic and morphometric analysis of 146 dried temporal bones obtained from adult cadavers. Twenty-two (15.0%) of the temporal bones presented persistent FH. Unilateral FH accounted for 4 (30.8%) and bilateral foramens for 18 (69.2%) of the 13 affected craniums. Forms varied, including 2 (7.8%) circular, 12 (46.1%) oval and 12 (46.1%) irregular FH. Ten (45.4%) of the temporal bones presenting FH were observed in the right side and 12 (54.6%) in the left. Mean size of FH was 3,00 mm in the transversal and 2,52 mm in the longitudinal axis. Additionally, the mean anterior and posterior distances from two adjacent anatomical structures, petrotympanic fissure, and styloid process were 4,23 mm and 9,9 mm respectively. In conclusion, there seemed to be a considerable morphological heterogeneity when comparing the persistent FH specimens. We, additionally, highlight the importance of clinicians and oral and maxillofacial surgeons know this condition and its anatomical implications.